Dietary content and eating behavior in ulcerative colitis: a narrative review and future perspective - Lingxi Qin; Wenliang Lv (Nutrition Journal)
Abstract Ulcerative colitis (UC) has experienced a steady increase in global incidence and prevalence recently. Current research into UC pathogenesis focuses on the complex interplay of genetic and environmental factors with the immune system and gut microbiome, leading to disruption of the intestinal barrier. Normally, the microbiome, intestinal epithelium, and immune system interact to maintain intestinal homeostasis. However, when this equilibrium is disturbed, a harmful cycle of dysbiosis, immune dysregulation, and inflammation emerges, resulting in intestinal barrier dysfunction and UC progression. Among various risk factors, diet significantly influences epithelial barrier integrity and architectural stability through both direct and indirect mechanisms, shaping the entire UC continuum from pre-clinical prevention to active phase treatment and remission maintenance. This review provides insights into the impact of dietary content and eating behaviors on UC, focusing on specific food, food groups, nutrients, and intermittent fasting, while providing a detailed explanation of why the gut microbiota may mediate the sustained effects of diet across all stages of UC. Additionally, it addresses the limitations of current studies, explores underexamined areas in UC dietary research and proposes potential directions for future research and expansion.